The relationship between burnout and quality of life among secondary school teachers in Kuala Kangsar, Perak, Malaysia - Norly, Norshasha Sorfina; Ab Razak, Ratna Roshida; Zakaria, Muhammad Hafeez (Human Resource Management Academic Research Society, 2023)
The purpose of this study is to determine the relationship between burnout and quality of life among secondary school teachers in Kuala Kangsar, Perak. There was a total of 56 respondents from 3 secondary schools in Kuala Kangsar participated voluntarily in this study. The data was collected through a set of a self-administered questionnaires. Two types of scales used in this study were the Maslach Burnout Inventory (MBI) to measure burnout and the WHOQOL-BREF to measure the quality of life. The results of this study revealed that emotional exhaustion was negatively correlated (r = -.561) (p = .000) with quality of life. Similarly, depersonalization also was negatively correlated (r = -.607) (p = .000) to quality of life. However, personal accomplishment was found to be positively correlated (r = .476) (p = .000) to the quality of life. The findings suggest that low emotional exhaustion and depersonalization, and high personal accomplishment experienced by teachers may contribute to a better quality of life as a whole. Ministry of Education and school administrators should work together to exercise healthy working conditions in schools to ensure a quality life for teachers. It is recommended for future studies to determine the effects of every burnout dimension on every domain of quality of life in detail. Furthermore, future research could be expanded in various states in Malaysia with an increased sample size to provide a greater generalization and yield more reliable data.